A New Contactless Fault Diagnosis Approach for Pantograph-Catenary System - Aydin, Ilhan; Karakose, Mehmet; Akin, Erhan (Czech Technical Univ Prague, 2012)
Railway transport is one of the most important mass transportation media in the worldwide. With the development of trains speed, safety and comfort levels of railways is getting more importance day by day. Besides high level of security requirement, detection of anomaly for rail and road shall be early identified for decreasing operation and maintenance expenditures. The pantograph-catenary system has an important role for collecting the current in electrical railways. The problem occurred in this system will affect the current collection performance of electrified trains. In this paper, a new image processing based technique is proposed to detect the arcing faults occurred between catenary and pantograph contact. The proposed method takes one frame from the digital camera and then the edge detection algorithm extracts the edges of pantograph. The arcing between contact wire and pantograph is detected by examining the position of contact wire of pantograph's edge.
15th International Conference on Mechatronics (Mechatronika) -- DEC 05-07, 2012 -- Prague, CZECH REPUBLIC
Keywords: pantograph; catenary; arcing faults; edge detection; fault diagnosis; railways